Woman and the labour market in East and West Germany: Socialist legacy and pre-socialist tradition - Michael Wyrwich (Friedrich Schiller University Jena, 2017)
There is a large and successful literature exploiting the division and re-unification of Germany as a natural experiment for analysing the effects of political regimes on economic behaviour. This paper contributes to this literature by reassessing the role of legacy effects of socialist labour market policies for explaining the much higher female labour force participation (FLFP) in East Germany as compared to West Germany. The starting point of the analysis is the empirical pattern that FLFP was already higher in the East before German separation. Applying difference-in-differences analyses on participation rates shows that there is, if anything, only a small long-term socialist treatment effect. Apparently, there is no effect in areas that have been either rural or heavily industrialized before German separation. In line with previous research, this study finds that there is an East German mark-up for social acceptance of maternal employment. An additional and novel finding of this study is that current social acceptance of maternal employment is also driven by pre-war differences in female labour supply. This corresponds to a remarkable mark-up of married East German women in the labour market before German separation that is also descriptively shown in the paper. Overall, the results suggest that potential legacy effects of socialism on attitudes toward working women do not necessarily translate into meaningful East-West differences in terms of actual female labour force participation.
Keywords: J16; J22; J23; N34; P25; P30; R23; 330; Attitudes toward work; Female labour force participation; Gender; Regional labour markets